The Relationship between ABO Blood Group Distribution and the incidence of Upper Gastric and Duodenal Ulcer in Iraqi Patients - Manal K. Abdulridha (College of Pharmacy University of Baghdad, 2017)
The relationship between blood group antigens and peptic ulcer disease has been widely evaluated in the past, but only one study relating H pylori seroprevalence to ABO blood groups among Iraqi patients with peptic ulcer disease is available. We aimed to evaluate the frequency of peptic ulcer disease among different ABO blood groups in Iraqi patients, and we thought it was worthwhile to try to determine whether these components take some part in disease etiology. One hundred and six patients with peptic ulcer disease (PUD) (43 male and 63 female; mean  age: 48 Â± 18 years) who attended Baghdad teaching hospital and Al- Yarmouk teaching hospital endoscopy centers were enrolled , and 238 control Subjects.  Finger blood samples were used for ABO/Rhesus (Rh) blood group antigen typing. The ABO blood group phenotype frequency in peptic ulcer patients was as follows: 18.9% for blood group A, 15.1% for blood group B, 57.5 % for blood group O and 8.5% for blood group AB.  Rh positivity was found in 100% of patients. Significant higher percentage of patients with both gastric and duodenal ulcer disease are those holding  blood group O+   compared to other blood group phenotypes  (57.5%)( p= 0.003) .The present study show higher incidence of doudenal ulcer( DU) in patients  with blood group O+ compared to gastric ulcer( GU)   patients (65.6%vs 54.1%) , although no  statistical difference between both diseases was found,( p Ëƒ 0.05) in respect to other blood  group phenotypes.   Peptic ulcer disease is predominant in patients aged between 50-59 years represents with higher percentage (26.4%) compared to other age groups.  Patients with blood group O+ phenotype presented with a highly significant percentage of Peptic ulcer disease, since those individuals may express a higher inflammatory responses to H. pylori with higher levels of lymphocyte infiltration in the gastrointestinal mucosa   , and a higher frequency of secretor status  . In addition, they do not produce the substance on the surface of blood group O+ cells that may protect the lining of the duodenum .According to these results, probably ABO/Rh blood group (mainly blood group O+)   has an important role in patients with peptic ulcer disease as additional risk . The functional significance of ABO blood group distribution might be associated with biological behavior of Peptic ulcer disease. The impact of blood group on Peptic ulcer disease may be a focus for further studies. Keywords:  ABO/ Rh Blood group system - Upper gastrointestinal disorders â€"Age &  Gender distribution